Long-term neurocognitive function and quality of life after multimodal therapy in adult glioma patients: a prospective long-term follow-up - Pertz, Milena; Schlömer, Sabine; Seidel, Clemens; Hentschel, Bettina; Löffler, Markus; Schackert, Gabriele; Krex, Dietmar; Juratli, Tareq; Tonn, Joerg Christian; Schnell, Oliver; Vatter, Hartmut; Simon, Matthias; et al. (Journal of neuro-oncology, 2023)
Purpose: Multimodal therapies have significantly improved prognosis in glioma. However, in particular radiotherapy may induce long-term neurotoxicity compromising patients’ neurocognition and quality of life. The present prospective multicenter study aimed to evaluate associations of multimodal treatment with neurocognition with a particular focus on hippocampal irradiation. Methods: Seventy-one glioma patients (WHO grade 1–4) were serially evaluated with neurocognitive testing and quality of life questionnaires. Prior to (baseline) and following further treatment (median 7.1 years [range 4.6–11.0] after baseline) a standardized computerized neurocognitive test battery (NeuroCog FX) was applied to gauge psychomotor speed and inhibition, verbal short-term memory, working memory, verbal and non-verbal memory as well as verbal fluency. Mean ipsilateral hippocampal radiation dose was determined in a subgroup of 27 patients who received radiotherapy according to radiotherapy plans to evaluate its association with neurocognition. Results: Between baseline and follow-up mean performance in none of the cognitive domains significantly declined in any treatment modality (radiotherapy, chemotherapy, combined radio-chemotherapy, watchful-waiting), except for selective attention in patients receiving chemotherapy alone. Apart from one subtest (inhibition), mean ipsilateral hippocampal radiation dose > 50 Gy (Dmean) as compared to < 10 Gy showed no associations with long-term cognitive functioning. However, patients with Dmean < 10 Gy showed stable or improved performance in all cognitive domains, while patients with > 50 Gy numerically deteriorated in 4/8 domains. Conclusions: Multimodal glioma therapy seems to affect neurocognition less than generally assumed. Even patients with unilateral hippocampal irradiation with > 50 Gy showed no profound cognitive decline in this series.